2014
DOI: 10.3828/tpr.2014.43
|View full text |Cite
|
Sign up to set email alerts
|

Transformational transport infrastructure: cost-benefit analysis challenges

Abstract: Institute for Transport Studies 38-40 University Rd University of Leeds Leeds LS2 9JT Research interests:James Laird (J.J. Laird@its.leeds.ac.uk): cost benefit analysis; value of travel time savings; rural transport appraisal; wider economic benefits; and demand forecasting.Chris Nash (C.A.Nash@its.leeds.ac.uk): rail transport; transport appraisal; transport pricing and externalities.Peter Mackie (P.J.Mackie@its.leeds.ac.uk): cost benefit analysis; transport appraisal, value of travel time savings; wider econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…However, this attempt to extend the cost-benefit analysis framework to encompass wider impacts may not be the most appropriate way forward to understanding the overall impact on regional development from a major HSR project. Laird et al (2014) have attempted to map out the requirements of an extended CBA approach and contrast this with an alternative view that tries to go straight to the impact on output or gross value added (GVA). Models that try to do this have been around for many years in the form of land-use transport interaction (LUTI) models (Wegener, 2011).…”
Section: Estimating Wider Impactsmentioning
confidence: 99%
“…However, this attempt to extend the cost-benefit analysis framework to encompass wider impacts may not be the most appropriate way forward to understanding the overall impact on regional development from a major HSR project. Laird et al (2014) have attempted to map out the requirements of an extended CBA approach and contrast this with an alternative view that tries to go straight to the impact on output or gross value added (GVA). Models that try to do this have been around for many years in the form of land-use transport interaction (LUTI) models (Wegener, 2011).…”
Section: Estimating Wider Impactsmentioning
confidence: 99%
“…Similar issues have been raised in the context of improving communications between the cities of Northern England (SERC, 2009). Laird et al (2014) have shown the limitations of conventional cost-benefit analysis in dealing with investments of this type. But attempts to go beyond conventional cost-benefit analysis approaches to try and capture this effect in terms of a direct impact on output (KPMG, 2013) have led to serious criticism, in terms of both the assumptions and the net result (Overman, 2013).…”
Section: !Introductionmentioning
confidence: 99%
“…The coverage of the CBAs of conventional HSR projects naturally varies from country to country, but as a rule, these analyses tend to cover the construction costs of transport projects, the operation and maintenance costs of associated transport services, direct user benefits, and a restricted list of externalities, such as transport safety impacts, congestion, overcrowding and emissions (Ollivier et al, 2014). However, there seems little doubt that there are wider impacts from HSR investment that are not captured by conventional CBA (Laird et al, 2014;Venables, 2007). In particular, the regional economic effect of a large-scale HSR network is considered nontrivial, which should be carefully estimated and added to the extended CBA.…”
Section: Literature Reviewmentioning
confidence: 99%